Acute poisoning in children: Ten years’ experience from a Northern Thai tertiary care center - Boonchooduang, Nonglak; Louthrenoo, Orawan (Biomedical Sciences and Clinical Medicine, 2018)
Objective Acute poisoning in children is a worldwide health problem. This study aimed to investigate patterns and features of acute poisoning in hospitalized children. Methods This retrospective study was conducted using clinical data of 62 children diagnosed with poisoning who were treated and discharged from hospitalized at Chiang Mai University Hospital between January 2007 and December 2016. Results The patients included 35 male and 27 female children age 6 months to 14 years 7 months, mean age 4.9±4.6 years. Among the 62 cases, 46 (74.2%) were less than 5 years old, and 49 (79.0%) were cases of unintentional poisoning. Among the poisoned children younger than 10 years most were males, whereas females predominated in those age 10 to 15 years. Medications were the most common poisoning agents, followed by household cleaning products, insecticides and pesticides, disc batteries, hydrocarbons, and others. The duration of hospitalization of the poisoned children ranged between 1 and 22 days; the mortality rate was 3.2% (2 children). Conclusions Acute poisoning was most prevalent in children younger than five years old. Most cases were unintentional ingestion of medications or household products found in the house. Pediatricians and health care providers should take a key role in providing guidance to parents regarding methods to avoid incidents of acute poisoning in children.